A Device for the Production of Well-Defined Lesions of Mesenteric Blood Vessels with Resulting Platelet Thrombi - Reber, K (Thrombosis and Haemostasis, 1966)
Well-defined lesions of mesenteric blood vessels with resulting platelet thrombi are produced in a reproducible manner by electric stimulation with a microelectrode under microscopic observation. The apparatus used and the results obtained are described.